The Influence of the Ability to Read and Write the Qur'an on the Learning Outcomes of Islamic Religious Education Students in Class VI A Darul Hikam Elementary School Bandung - Asep Wahyu; Basuki; Abdul Karim Karim; Endah Nurdini (Global Writing Academica Researching and Publishing, 2022)
This study aimed to determine the influence of the ability to read and write the Qur’an on the learning outcomes of Islamic Religious Education students in grade VI A. This research approach uses a quantitative approach. This type of research uses survey research. In taking samples using Stratified Proportionate Random Sampling. For data collection techniques using tests and documentation. Methods of data analysis using simple linear regression test and multiple linear regression test. Based on the analysis and research discussion, it can be concluded that 1) the ability to read the Qur'an influences the learning outcomes of students' Islamic education; 2) The ability to write the Qur'an does not affect students' Islamic Religious Education Learning Outcomes, and 3) The ability to read the Qur'an and the ability to write the Qur'an together influence the learning outcomes of students' Islamic education.